Producing Silicon Carbide Micro and Nanostructures by Plasma‐Free Metal‐Assisted Chemical Etching. (10th June 2021) - Michaels, Julian A.; Janavicius, Lukas; Wu, Xihang; Chan, Clarence; Huang, Hsieh‐Chih; Namiki, Shunya; Kim, Munho; Sievers, Dane; Li, Xiuling
Abstract: Silicon carbide (SiC) is a wide bandgap third‐generation semiconductor well suited for harsh environment power electronics, micro and nano electromechanical systems, and emerging quantum technology by serving as hosts for quantum states via defect centers. The chemical inertness of SiC limits viable etching techniques to plasma‐based reactive ion etching methods; however, these could have significant undesirable effects for electronic and photonic devices. This paper presents a plasma‐free, open‐circuit, photo‐induced metal‐assisted chemical etch for fabricating micro and nanoscale features without the inherent high energy ion‐related surface damage. The method presented herein utilizes above bandgap ultraviolet light, patterned noble metal (Pt), and a solution consisting of an oxidant potassium persulfate (K2 S2 O8 ) and an acid, hydrofluoric acid, to spatially define the etching morphology. The parameter space is comprehensively explored to demonstrate the controllability and versatility of this technique to produce ordered arrays of micro and nanoscale SiC structures with porous or solid sidewalls, and to elucidate the etching mechanism. Abstract : Silicon carbide periodic hole arrays are produced via photo‐enhanced‐metal‐assisted chemical etching. This is an open‐circuit, plasma‐free, metal‐catalyzed highly‐anisotropic etching method. The surface morphology including porosity and smoothness can be tuned by the etch condition, potentially useful for power electronics, MEMS, and quantum technologies.